1996
DOI: 10.1021/la951051q
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination of AOT/n-Hexane/Water/Urea Reversed Micelles by Light and Small Angle X-ray Scattering

Abstract: The structural effect of urea in sodium bis(2-ethylhexyl) sulfosuccinate (AOT)/n-hexane/water reversed micelles (RM) at molar concentration ratio [water]/[AOT] = 10 is investigated by light and small angle X-ray scattering techniques. Scattering intensities are analyzed within the framework of repulsion and attractive interaction potentials due to RM excluded volume (hard sphere term) and contact adhesion (attractive term). In the absence of urea the simple hard sphere droplet model up to a RM volume fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Recent experiments that support our reasoning are the light scattering measurements by Politi et al. They observed an increase in the hydrodynamic radius of water droplets in the presence of high concentrations of urea which means that interfacial area is not changing with urea. This indicates that the presence of urea in the AOT film produces only disorganization of the interface, rendering it more flexible and fluid and as a result leading to an increase in the interdroplets attractive interaction.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Recent experiments that support our reasoning are the light scattering measurements by Politi et al. They observed an increase in the hydrodynamic radius of water droplets in the presence of high concentrations of urea which means that interfacial area is not changing with urea. This indicates that the presence of urea in the AOT film produces only disorganization of the interface, rendering it more flexible and fluid and as a result leading to an increase in the interdroplets attractive interaction.…”
Section: Discussionsupporting
confidence: 80%
“…This indicates that the presence of urea in the AOT film produces only disorganization of the interface, rendering it more flexible and fluid and as a result leading to an increase in the interdroplets attractive interaction. The larger values of hydrodynamic radius were related by Politi et al to interpenetration of the surfactant tails, due to attractive forces, which leads to a greater effective radius for light scattering observations. X-ray scattering results 31 indicate that the structure of the discrete spherical droplets is kept after the percolation phenomenon.…”
Section: Discussionmentioning
confidence: 92%
“…4b shows the calcined mesoporous material obtained with DDAB + TiO 2 , showing a more disordered material. Lamellae are present but are smaller Costa Amaral et al [27] studied AOT/water/n-hexane micelles with [H 2 O]/[AOT] = 10. They found a micelle aggregation number n = 202 ± 15.…”
Section: Tem Photomicrographsmentioning
confidence: 99%
“…RMs offer a completely different perspective on the chaotropic action of urea on surfactants since they have water confined in nanodimensions. The effect of urea on reverse microemulsion structure and dynamics has extensively been studied for AOT microemulsions. The modulation of attractive and repulsive interactions at the reverse micellar (RM) interface has been studied in AOT (sodium dioctyl sulfosuccinate)/ n -hexane/water/urea reverse micelles using a combination of light scattering and small-angle X-ray scattering experiments. , From light and small-angle X-ray scattering experiments, Amaral et al observed significant intermicellar attraction, which induced RM droplet clustering and subsequently, percolation. In a related study, Itri et al used the polydisperse hard sphere model as the form factor and Baxter’s sticky hard sphere model as the structure factor to analyze the small-angle X-ray scattering from AOT reverse micelles RMs.…”
Section: Introductionmentioning
confidence: 99%